Vertical response of unbonded fiber reinforced elastomeric isolators (U-FREIs) under bidirectional shear loading - Galano, Simone (Frontiers in Built Environment, 2022)
Fiber Reinforced Elastomeric Isolators (FREIs) were generally studied in unbonded configuration. Due to combined axial and shear loads, the contact area between the bearing and horizontal supports reduces with the horizontal displacement. As a result, both the vertical and the horizontal stiffnesses decrease with the horizontal deformation while also vertical displacement increases. This paper presents the results of a large set of full-scale 3D Finite Element Analyses on unbonded fiber reinforced bearings with different geometries, subjected to combined axial and multi-directional shear loads. The main vertical response parameters were studied, namely the vertical displacement, the vertical stiffness, and the effective compressive modulus, thus highlighting the influence of both geometry and horizontal loading direction on the vertical response of the FREIs. Conclusions of this study demonstrate to what extent the combined influence of geometric properties and loading conditions affects the vertical response of fiber reinforced bearings.